The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/jor.24880
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy‐activated nucleus pulposus cells deliver exosomal miR‐27a to prevent extracellular matrix degradation by targeting MMP‐13

Abstract: Although autophagy may be beneficial for maintaining the metabolic balance of the extracellular matrix (ECM) in the nucleus pulposus (NP) and its vitality under inflammation, the underlying mechanism still remains unclear. A previous study found that autophagy activation stimulated the release of exosomes in normal chondrocytes, which are located in a similar avascular environment and share many common features with those of nucleus pulposus cells (NPCs). This study explored the protective effect on matrix deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…The expression of miR-27a was detected by qRT-PCR for identification of successful transfection ( Figure 5A ). It has been reported that MMP-13 was a direct target of miR-27a ( Zhang et al, 2020 ). MiR-27a-mimics transfection effectively decreased the expression of GAS5 ( Figure 5B ) and MMP-13 ( Figures 5C–E , G-H ) and increased the expression of Col2a1 ( Figures 5D,F ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of miR-27a was detected by qRT-PCR for identification of successful transfection ( Figure 5A ). It has been reported that MMP-13 was a direct target of miR-27a ( Zhang et al, 2020 ). MiR-27a-mimics transfection effectively decreased the expression of GAS5 ( Figure 5B ) and MMP-13 ( Figures 5C–E , G-H ) and increased the expression of Col2a1 ( Figures 5D,F ).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, miR-27a expression was significantly decreased in mechanical stimulation-treated chondrocytes. MMP-13 was a direct target of miR-27a ( Zhang et al, 2020 ), and miR-27a was a direct target of GAS5. Overexpression of miR-27a greatly decreased the expression of MMP-13 and GAS5 and increased the expression of Col2a1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-199a decreased MMP-2, MMP-6, TIMP-1 and apoptotic cells in a mouse model of IDD, while the expression of collagen type II, aggrecan, increased following the exposition to BMSC EVs in vitro [134]. Among other miRNAs previously identified, miR-27a was involved in the regulation of apoptotic pathways and in the prevention of IDD through the ability to suppress ECM degradation targeting MMP-13 [135,136]. Similarly, under TNF-α stimulation, exosomes extracted from BM-MSCs were able to secrete miR-532-5p.…”
Section: The Role Of Mirnas In Iddmentioning
confidence: 92%
“…The exosome-depleted FBS was obtained by ultracentrifugation, as described below. The medium was collected after 36 h of 10 ng/mL TNF-α pretreatment, followed by gradient centrifugation to remove debris, and ultracentrifugation at 120,000 ×g for 120 min, as previously described (17). The pellet was resuspended in PBS, quantified by bicinchoninic acid (BCA) protein assay (Beyotime, China), and cryopreserved at −80 ℃.…”
Section: Exosome Isolation and Identificationmentioning
confidence: 99%
“…Many studies have reported the protective role played by exosomal miRNAs that are derived from the cells involved in disc degeneration diseases, such as IDH (13)(14)(15)(16). Recently, we reported that the exosomal miR-27a derived from autophagyactivated healthy NPCs could repress IL-1β-induced NP matrix degradation by targeting matrix metalloprotease 13 (MMP-13) (17).…”
Section: Introductionmentioning
confidence: 99%